A community called atonement - McKnight, Scot (Nashville : Abingdon Press, 2007)
"Over the centuries the church developed a number of metaphors, such as penal substitution or the ransom theory, to speak about Christ's death on the cross and the theological concept of the atonement. Yet too often, says Scot McKnight, Christians have held to the supremacy of one metaphor over against the others, to their detriment. He argues instead that to plumb the rich theological depths of the atonement, we must consider all the metaphors of atonement and ask whether they each serve a larger purpose. A Community Called Atonement is a constructive theology that not only values the church's atonement metaphors but also asserts that the atonement fundamentally shapes the life of the Christian and of the church. That is, Christ identifies with humans to call us into a community that reflects God's love (the church)--but that community then has the responsibility to offer God's love to others through missional practices of justice and fellowship, living out its life together as the story of God's reconciliation. Scot McKnight thus offers an accessible, thought-provoking theology of atonement that engages the concerns of those in the emerging church conversation and will be of interest to all those in the church and academy who are listening in" --Amazon.com.
pt 1. Atonement and convergence : where to begin? With Jesus, of course! ; With God, with eikons, and with sin, too ; With eternity, with ecclesial community, and with praxis, too -- pt 2. Atonement and image: with which image? Atonement as metaphor : metaphor and mechanics ; The mystery of our metaphors : an exercise in postmodern humility ; Atoning moments : crux sola? ; Atoning moments : incarnation as second Adam ; Atoning moments : crucifixion ; Atoning moments : Easter and Pentecost -- pt 3. Atonement as story : whose story? The story of Jesus : Passover ; The story of Paul : in the courtroom of God ; The story of early theologians : Irenaeus and Athanasius ; Which is the fairest of them all? -- pt 4. Atonement as praxis : who does atonement? Atonement as missional praxis : fellowship ; Atonement as missional praxis : justice ; Atonement as missional praxis : missional ; Atonement as misisonal praxis : living the story of the word ; Atonement as missional praxis : baptism, eucharist, and prayer.
Includes bibliographical references (pages 157-168) and indexes.
Keywords: Atonement; Atonement -- Biblical teaching; Mission of the church